2010
DOI: 10.1007/s10646-010-0500-5
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR synthesis as response to nitrogen: transcriptional analysis of the mcyD gene in Microcystis aeruginosa PCC7806

Abstract: The influence of environmental factors on microcystin production by toxic cyanobacteria has been extensively studied. However, the effect of nitrogen on the synthesis of this toxin remains unclear because of the literature contradictory data. The aim of this work was to determine how nitrate affects the transcriptional response of mcyD gene and the microcystin-LR synthesis in Microcystis aeruginosa PCC 7806. For first time real time RT-PCR has been used to investigate the effect of nitrogen availability. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 25 publications
2
44
0
1
Order By: Relevance
“…Nevertheless, the lowest nitrate concentration used by these authors (0.2 mmol liter Ϫ1 ) was not as low as in our experiments or in experiments by Ginn and Neilan, and this is probably the reason for the difference in their results. For example, in this study, we used a nitrate concentration about 20 times lower (0.01 mmol liter Ϫ1 ) than that used by Sevilla et al (23), and Ginn and Neilan (24), who found results similar to ours, used an entirely N-depleted medium (no nitrate addition). Conflicting results occur mainly because investigations on regulatory mechanisms of toxin production have not yet been standardized and experimental designs and growth controls are frequently different; therefore, outputs tend to be controversial (7).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Nevertheless, the lowest nitrate concentration used by these authors (0.2 mmol liter Ϫ1 ) was not as low as in our experiments or in experiments by Ginn and Neilan, and this is probably the reason for the difference in their results. For example, in this study, we used a nitrate concentration about 20 times lower (0.01 mmol liter Ϫ1 ) than that used by Sevilla et al (23), and Ginn and Neilan (24), who found results similar to ours, used an entirely N-depleted medium (no nitrate addition). Conflicting results occur mainly because investigations on regulatory mechanisms of toxin production have not yet been standardized and experimental designs and growth controls are frequently different; therefore, outputs tend to be controversial (7).…”
Section: Discussionmentioning
confidence: 69%
“…Ginn and Neilan (24) also observed an increase in the transcription of the mcy gene under conditions of nitrate starvation. However, Sevilla et al (23) showed that while a decrease of nitrate caused lower cell growth, it did not directly affect mcy transcription or toxin production. Nevertheless, the lowest nitrate concentration used by these authors (0.2 mmol liter Ϫ1 ) was not as low as in our experiments or in experiments by Ginn and Neilan, and this is probably the reason for the difference in their results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transcriptional results confirm that synthesis of MC is related to cell division and growth, although the amount of produced MC, is regulated in response to environmental factors such as light (Kaebernick et al 2000;Kim et al 2005;Tonk et al 2005) and trace elements (iron) (Sevilla et al 2008). On the contrary, availability of macronutrients (nitrogen), although being often showed to affect MC synthesis (Lee et al 2000), does not seem to influence mcyD expression (Sevilla et al 2010). Under phosphate starvation, the nine genes of the ndaS cluster are constitutively overexpressed, up to a 2.73-fold, in N. spumigena strain AV1, probably due to transcription from the single bidirectional promoter (Jonasson et al 2008).…”
Section: Assessment Of Hepatotoxin Biosynthetic Genes Transcriptionalmentioning
confidence: 98%
“…To identify the factor(s) governing massive cyanobacterial growth, numerous studies have investigated the role of biological, physicochemical, and hydrological elements in the ecosystems (Oberholster et al, 2009;Paerl and Huisman, 2008;Van Wichelen et al, 2010). A large number of studies have also examined the environmental factors influencing the production of microcystin by Microcystis species (Sevilla et al, 2010;Xu et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%